Drama of multilingualism : literature review and liberation - Aleksić, Gabrijela (Advances in cultural psychology., 2022)
This book is a synthesis of important topics in studying multilingualism: dynamic multilingualism, translanguaging, language policy, bilingual education, and bilingualism and cognition. The author as an immigrant herself integrated personal and dramatic experiences around most of the topics to show how they influence the lives of immigrants around the globe. The author's aim is to reach the readers in a personal way. The issue of translanguaging and social justice is crucial for the book. The studies on bilingualism and cognition give amazing results on how bilingual children profit from increased metalinguistic awareness, abstract thinking, creativity, working memory, attention control, to name just a few. Bilingualism is shown to be a real gift for human understanding.The original feature of this book is the integration of excerpts of the interviews the author conducted with the experts in the field of bilingualism: Ellen Bialystok, Jim Cummins, Ofelia Garcí a, Christine He lot, Nancy Hornberger, and Catherine Snow. For each topic their opinions are combined with future directions in the research on bilingualism that can certainly inspire other researchers in the field. Finally, this book is called Drama of Multilingualism: Literature Review and Liberation, and it is exactly that, informing and affecting those who want to embark on this dramatic journey of exploring multilingualism.